Social computing. second International Conference of Young Computer Scientists, Engineers and Educators, ICYCSEE 2016, Harbin, China, August 20-22, 2016, Proceedings /: second International Conference of Young Computer Scientists, Engineers and Educators, ICYCSEE 2016, Harbin, China, August 20-22, 2016, Proceedings. Part I : (2016) - Unknown
No abstract available